Creating Aptamers and Their Use in Resisitive Pulse Sensors. (2017) - Platt, Mark
Abstract: Resistive pulse sensors, RPS, are allowing the transport mechanism of molecules, proteins and even nanoparticles to be characterized as they traverse small channels. Here we present our recent advancement of the technique identifying key experimental designs for potential POC assays. The first assay utilized superparamagnetic beads, if the surfaces of the beads are modified with an aptamer, the frequency of beads (translocations/minute) through the pore can be related to the concentration of specific proteins in the solution. Herein, we have demonstrated the successful use of TRPS to observe the binding of two proteins, to their specific aptamers simultaneously. We then adapt the measurement strategy and demonstrate that the translocation times of particles can be used to infer the zeta potential to measure the change in zeta potential of DNA modified particles. By measuring the translocation times of DNA modified nanoparticles as a function of packing density, length, structure, and hybridisation time, we observe a clear difference in zeta potential using both mean values, and population distributions as a function of the DNA structure. Finally we present the first comparison between assays that use resistive pulses or rectification ratios on a tunable pore platform.